AHP - SAW DECISION SUPPORT SYSTEM FOR AI-BASED TEACHING MATERIAL RECOMMENDATION - Muhammad Amin; Hainur Rasyid; Akmal Akmal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2026)
Abstract: The development of Artificial Intelligence (AI) in education provides significant opportunities for supporting the development of English teaching materials in elementary schools. However, the wide variety of available AI tools makes it difficult for teachers to select the most appropriate tools for their instructional needs. This study aims to analyze and generate recommendations for AI utilization using a Decision Support System (DSS) based on the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods. The AHP method is used to determine the weight of criteria based on their importance, while the SAW method is applied to rank alternative AI tools. This study involves teachers at SDN 15 Padang Genting in identifying criteria and evaluating alternatives. The results show that the proposed DSS model is capable of generating appropriate AI tool recommendations based on predefined criteria. This approach contributes to more objective and systematic decision-making in utilizing AI for developing English teaching materials in elementary education. Keywords: analytical hierarchy proces; artificial intelligence; decision support system; simple additive weighting; teaching materials Abstrak: Perkembangan Artificial Intelligence (AI) dalam pendidikan memberikan peluang dalam penyusunan bahan ajar Bahasa Inggris di sekolah dasar. Namun, banyaknya pilihan tools AI menyebabkan guru mengalami kesulitan dalam menentukan tools yang paling sesuai dengan kebutuhan pembelajaran. Penelitian ini bertujuan untuk menganalisis dan menghasilkan rekomendasi pemanfaatan AI menggunakan Sistem Pendukung Keputusan (SPK) berbasis metode Analytical Hierarchy Process (AHP) dan Simple Additive Weighting (SAW). Metode AHP digunakan untuk menentukan bobot kriteria berdasarkan tingkat kepentingannya, sedangkan metode SAW digunakan untuk melakukan perangkingan alternatif tools AI. Penelitian ini melibatkan guru di SDN 15 Padang Genting dalam proses identifikasi kriteria dan penilaian alternatif. Hasil penelitian menunjukkan bahwa model SPK mampu menghasilkan rekomendasi tools AI yang sesuai dengan kebutuhan pengguna berdasarkan kriteria yang telah ditentukan. Pendekatan ini memberikan kontribusi dalam mendukung pengambilan keputusan yang lebih objektif dan sistematis dalam pemanfaatan AI untuk penyusunan bahan ajar Bahasa Inggris di sekolah dasar. Kata kunci: analisis proses hierarki; bahan ajar; kecerdasan buatan; sistem pendukung keputusan; simple additive weighting.